Legal Regulation of Inheritance of Non-Fungible Tokens - E. I. Leskina (Теоретическая и прикладная юриспруденция)
The development of digital technologies permeates almost all areas of public relations. At the same time, certain areas remain more conservative, and legal regulation also lags behind the pace of general digitalization. This situation is especially clearly visible in the field of inheritance of digital assets. The subject of this article is to explore the opportunities and risks associated with inheriting NFTs. The purpose of the article is to determine algorithms for inheriting NFTs in the context of insufficient legal regulation of this procedure in the Russian Federation. The work uses methods of both empirical (analysis and synthesis, induction and deduction, systematization) and theoretical (methods of constructing and studying the object of study and methods of constructing and justifying theoretical knowledge) levels. When transferring a token, a unique record is transferred, and the previous owner of the NFT loses the token after it is transferred. This makes NFTs similar to material objects and necessitates separate legal regulation of the rights associated with NFTs. An NFT is inherited, not a digital object such as art. The main problem with inheriting NFTs is that these objects are intangible. They cannot be physically materialized, stored, for example, in a safe deposit box, or transferred physically. Therefore, if the owners do not have specific heirs, it will even be difficult to include NFT in the inheritance or find out about the token. Inheriting an NFT requires that the will name the NFT and include an explanation of where the NFT is held. The testator’s password must also be available. There may be problems associated with the compulsory share in the inheritance, related both to access and to the assessment and dynamically changing value of the NFT. Also, the valuation of the NFT will influence the amount of the state fee for issuing a certificate of inheritance. The practical implementation of NFT inheritance is facilitated by the development of appropriate digital technologies that optimize procedural aspects.